2011
DOI: 10.1038/nchem.1198
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic multi-component covalent assembly for the reversible binding of secondary alcohols and chirality sensing

Abstract: Reversible covalent bonding is often employed for the creation of novel supramolecular structures, multi-component assemblies, and sensing ensembles. In spite of remarkable success of dynamic covalent systems, the reversible binding of a mono-alcohol with high strength is challenging. Here we show that a strategy of carbonyl activation and hemiaminal ether stabilization can be embodied in a four-component reversible assembly that creates a tetradentate ligand and incorporates secondary alcohols with exceptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
125
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(127 citation statements)
references
References 59 publications
1
125
0
1
Order By: Relevance
“…This chiral sensor can be used for determination of the enantiomeric excess of mixed chiral alcohols with different ee values ( Figure 131B). 373 A chiral sensor with the ability to differentiate many different chiral molecules, such as amino acids, peptides, proteins, and even some aromatic drugs, has been developed by Biedermann and Nau. These systems are based on ternary complexes formed between the macrocyclic host cucurbit [8]uril, dicationic dyes, and chiral aromatic analytes ( Figure 132A).…”
Section: Supramolecular Chiral Recognition and Sensingmentioning
confidence: 99%
“…This chiral sensor can be used for determination of the enantiomeric excess of mixed chiral alcohols with different ee values ( Figure 131B). 373 A chiral sensor with the ability to differentiate many different chiral molecules, such as amino acids, peptides, proteins, and even some aromatic drugs, has been developed by Biedermann and Nau. These systems are based on ternary complexes formed between the macrocyclic host cucurbit [8]uril, dicationic dyes, and chiral aromatic analytes ( Figure 132A).…”
Section: Supramolecular Chiral Recognition and Sensingmentioning
confidence: 99%
“…However, quite unexpectedly, the reaction between 4AP and OV that has not been earlier reported in the literature led exclusively to hemiaminal ether or undefined polymeric products. In the last few years, direct formation of aminoethers was observed for the reactions of pyridyl aldehydes and/or pyridylamines, but these reactions were usually performed in the presence of metal cations and the products were isolated as metal complexes [26][27][28]. Formation of hemiaminal ethers was also observed in the presence of molecular sieves [29].…”
Section: Introductionmentioning
confidence: 99%
“…For example, various stereodynamic systems that utilize circular dichroism (CD) for ee determination have been published 12,13,17. Recently, our group developed a chiral alcohol sensor involving a multicomponent assembly that incorporates the alcohol into a hemiaminal ether ( 1 ) under equilibrium conditions1315 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…2, Y ) was expected to similarly alter the dr values due to different interactions with the axial metal ligand ( L ). Because we have previously found that larger dr values result in larger CD signals and lower errors in ee determination,1315 the goal of our substitutent effect studies was to enhance the dr's.…”
Section: Introductionmentioning
confidence: 99%